2001
DOI: 10.1046/j.1469-0705.2001.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy in chromosomally normal fetuses with increased nuchal translucency in the first trimester

Abstract: Increased fetal nuchal translucency is associated with chromosomal abnormalities, many fetal defects and genetic syndromes. In the majority of cases a series of antenatal investigations, including fetal karyotyping, detailed scans, fetal echocardiography, as well as genetic testing and infection screening, that can be completed by 20 weeks of gestation would distinguish between the pregnancies destined to result in adverse outcome and those leading to the delivery of infants without major defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
234
1
33

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(297 citation statements)
references
References 71 publications
(11 reference statements)
22
234
1
33
Order By: Relevance
“…Previous studies in singleton pregnancies have reported that an increased NT in a fetus with normal karyotype was associated with a poor pregnancy outcome, the chances of which increased exponentially with increasing NT thickness, from 8% when NT ranged between the 95 th and 99 th percentiles to 80-85% when the NT was above 6.5 mm 1,14 . While establishing our reference ranges for NT, we found the 99 th percentile not to be a fixed value, as has been described by other groups 1,15 , but to increase, from 2.27 mm at 45 mm CRL to 3.78 mm at 84 mm 11 . In our series, twins with an NT > 99 th percentile and normal karyotype had a 60% prevalence of fetal anomalies and a 20% risk of fetal demise, irrespective of chorionicity.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies in singleton pregnancies have reported that an increased NT in a fetus with normal karyotype was associated with a poor pregnancy outcome, the chances of which increased exponentially with increasing NT thickness, from 8% when NT ranged between the 95 th and 99 th percentiles to 80-85% when the NT was above 6.5 mm 1,14 . While establishing our reference ranges for NT, we found the 99 th percentile not to be a fixed value, as has been described by other groups 1,15 , but to increase, from 2.27 mm at 45 mm CRL to 3.78 mm at 84 mm 11 . In our series, twins with an NT > 99 th percentile and normal karyotype had a 60% prevalence of fetal anomalies and a 20% risk of fetal demise, irrespective of chorionicity.…”
Section: Discussionsupporting
confidence: 74%
“…In chromosomally normal fetuses, increased NT is associated with a wide range of fetal defects and genetic syndromes 5,12 . In addition, increased NT may also be a marker that predicts postnatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In chromosomally normal fetuses, increased NT is associated with a wide range of fetal defects and genetic syndromes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Most literature has focused on the individual components of the screen; increased fetal NT (Adekunle et al, 1999;Souka et al, 2001;Cheng et al, 2004;Dugoff et al, 2004;Kabili et al, 2004;Krantz et al, 2004), low maternal PAPP-A (Ong et al, 2000;Ochshorn et al, 2001;Yaron et al, 2002a;Kwik and Morris, 2003;Dugoff et al, 2004;Kabili et al, 2004;Krantz et al, 2004) and abnormal free *Correspondence to: Sandie L. Barrett, Western Diagnostic Pathology, Symbion Health, Western Australia, Australia. E-mail: sandieb@aapt.net.au β-hCG levels (Ong et al, 2000;Yaron et al, 2002b;Dugoff et al, 2004;Kabili et al, 2004;Krantz et al, 2004) and their associations with adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%